Are Ratings of Perceived Exertion during Endurance Tasks of Predictive Value? Findings in Trunk Muscles Require Special Attention - Christoph Anders; Lena Simone Mader; Max Herzberg; Christin Alex (Journal of Functional Morphology and Kinesiology)
Background: Subjective rating scales of perceived exertion are often used to quantify effort levels during various endurance exercises, particularly submaximal tasks. The aim of the current study was to determine whether predictive conclusions can be drawn from perceived exertion levels surveyed at the start of defined submaximal endurance tasks. Methods: In this study, healthy participants performed a 10-min endurance task at 50% of their upper body weight, targeting either the back muscles (n = 47, 24 women) or abdominal muscles (n = 32, 17 women). At the end of each minute, participants were asked to rate their perceived exertion (RPE) using the 14-points Borg Scale. Based on their initial and final RPE levels, and for each muscle group separately, participants were divided into subgroups reflecting low (good start/good end) and high (bad start/bad end) strain levels. These values were then compared over the duration of the exercise. Comparisons of RPE levels between subgroups were made using the Mann-Whitney U-test for independent samples, with Bonferroni-Holm correction to account for multiple comparisons. Results: Overall, strain levels increased throughout the duration of the exercise. For the abdominal muscles, the difference between the two RPE groups remained constant over time: participants with good start/end ratings consistently showed different strain levels from those with bad start/end ratings, regardless of whether the grouping was based on initial or final exertion levels. In contrast, for the back muscles, the initial grouping showed a crossover in strain values: by the end of the task, participants in the good start group tended to report higher strain than those in the bad start group. No differences were found in initial RPE values when the grouping was based on final exertion levels. Conclusions: For endurance tasks involving the abdominal muscles, initial strain levels have strong predictive value, whereas this is not the case for the back muscles. Because back muscles are frequently loaded, continuous monitoring of RPE levels is necessary to prevent unexpected task failure, as initial RPE values are not predictive. In contrast, RPE values of 11 or higher on the 14-points Borg scale predict complete exhaustion or even premature task failure with high certainty for abdominal muscle exercises, while lower RPE levels indicate that exercise intensity can be increased.